HUBUNGAN ANTARA PENGUASAAN KOSAKATA DENGAN KEMAMPUAN MENULIS CATATAN HARIAN PADA SISWA KELAS VII MTs MATHLA’UL ANWAR PUSAT MENES KABUPATEN PANDEGLANG - Ade Juanto (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2020)
ABSTRACT The Relationship Between Vocabulary Mastery and Daily Notes Writing Ability in Grade VII Students of MTs Mathla'ul Anwar, Menes Center, Pandeglang RegencyThe background of this problem is helping children improve their ability to communicate with Indonesian properly and correctly, both verbally and in writing. One form of the ability to communicate verbally can be poured in the form of ability in mastering vocabulary. Vocabulary is a form of words in a language, both known (mastered) or unknown (not yet mastered).The purpose of this study was to determine the relationship between vocabulary mastery and the ability to write a diary in grade VII students of Maths Maul Anwar Center for Menes in the Academic Year of Pandeglang Regency.This research was conducted at the MTs Mathla'ul Anwar Center of Menes in the odd semester of the 2018/2019 Academic Year, which was located on the Prapatan Cimanying Menes Pandeglang-Banten highway, Class VII of the odd semester of the 2018/2019 Academic Year.Data collection techniques used in this study are tests that will be used to obtain variables related to the relationship between vocabulary mastery and the ability to write a diary in class VII students of Maths' Anwar Anwar Center Menes Pandeglang RegencyThe analysis requirements test used is the normality test and the homogeneity test. The calculation of normality test uses a significance level of 5%, while the homogeneity test uses the similarity test of two variances. From the results of the normality test results obtained in the mastery of vocabulary X ¬2 ¬calculate 5.52 and the ability of the daily record X ¬ ¬2calculate 3.17. X2 table on vocabulary mastery and the ability to write a diary with db = k -3 = 5-3 = 2 and ? = 5% is 5.991. Because in the two groups X ¬ 2 ¬ arithmetic <X 2 table then it can be concluded the data of the two groups are normally distributed. For the homogeneity test, Fcount = 1.01 with Ftable = 1.90, because Fcount <Ftable, it can be concluded that the data is homogeneous.To determine the strength of the comparison hypothesis test is used and the obtained value of tcount = 19.8 with a significant level ? = 5% and degrees of freedom (dk) = 30-2 = 28 obtained ttable 1.71. Because tcount> ttable, meaning reject Ho, which states that there is a relationship between vocabulary mastery and the ability to write a diary in grade VII students of MTs Mathla'ul Anwar Center of Menes Pandeglang Regency.Keywords: Vocabulary Mastery, Writing Daily Notes.